Multiple-model description and generalised algorithm of ship-building wharf scheduling. (24th April 2019) - Sokolov, Boris; Zelentsov, Vyacheslav; Potryasaev, Semyon; Kalinin, Vladimir; Tolpegin, Oleg
We present a new multiple-model description and generalised algorithm of ship-building wharf scheduling. This description is represented as a special case of the job-shop-scheduling problem with dynamically distributed jobs, resources, flows, structures. The approach is based on a natural dynamic decomposition of the problem and its solution with the help of a modified form of continuous maximum principle coupled with combinatorial optimisation.